Cold-bonding process for treatment and reuse of waste materials: Technical designs and applications of pelletized products. Issue 19 (2nd October 2021) - Ferraro, Alberto; Colangelo, Francesco; Farina, Ilenia; Race, Marco; Cioffi, Raffaele; Cheeseman, Christopher; Fabbricino, Massimiliano
Abstract: This work provides a comprehensive review of research on the cold-bonding pelletization process used to produce lightweight aggregates (LWAs) using waste materials, to valorize the waste and, at the same time, minimize risks related to disposal. Research investigating various aspects of the cold-bonding process highlight: i) feasible mix-designs for pellet production; ii) the most relevant operating parameters affecting the process; and iii) the potential applications of the LWAs produced. The analysis gives a wide overview of the fundamental key-points that control the cold-bonding process. Data comparison provides a useful way to identify the optimal process conditions to allow development of optimum products. This involves the selection of the correct mix-design, including suitable binders and potential additives, and the selection of appropriate operating conditions, which are a function of the waste investigated, and/or waste mix characteristics. The review proposes an optimized approach to experimental studies on cold-bonding processes that has potential to enhance future process performance. Moreover, the present work provides a complete framework useful for decision-making for both manufacturers and researchers working to use this promising technique. Graphical abstract: UF0001